The Anatase-to-Rutile Phase Transition in Highly Oriented Nanoparticles Array of Titania with Photocatalytic Response Changes - Olga Boytsova; Irina Zhukova; Artem Tatarenko; Tatiana Shatalova; Artemii Beiltiukov; Andrei Eliseev; Alexey Sadovnikov (Nanomaterials, 2022)
An array of highly oriented anatase nanoparticles was successfully prepared from NH4TiOF3 with the assistance of polyetheleneglycol-400 at 450 °C. The study showed the stability of obtained layered TiO2-anatase close to 1200 °C. This research confirmed for the first time that the transition of mesocrystalline anatase to the rutile phase occurs between 1000 °C and 1200 °C, which is more than 400 °C higher than the transition of bulk TiO2 due to the used precursor. A small quantity of K-phase nanowhiskers, which issued after 800 °C in the composite based on TiO2, stimulated a fourfold increase in photocatalytic performance. This study offers a new approach to the construction and preparation of effective nanocrystalline photocatalyst.